A New Formulation of 99mTc-Macroagreggated Albumin (MAA) Freeze-dried Kit for Lungs Scintigraphy - Alaa K. Jabbar; Adeeb Abass Al-shami; Husham M. Abdulkarim (College of Pharmacy / Mustansiriyah University, 2008)
A new formulation of macro aggregated albumin (MAA) to be labeled with 99mTc was prepared by a simple and fast method. The suspension of macroagreggated albumin was prepared by diluting 0.4ml human serum albumin (200mg/ml) with normal saline (sterilized and pyrogen free) Concentrated hydrochloric acid was added to denature the protein and this step was followed by the addition of tin in the form of stannite . 3.5ml of polyethylene glycol (PEG) (1mg/ml) was also added to act as antiagglomerating agent. The pH was adjusted to 5.2 with NaOH and the suspension was heated with continuous stirring to get aggregation The vials contents were allowed to react with 99mTc and high radiochemical purity was obtained (greater than 95%) after 15min. 99mTc-MAA was stable for at least six hours. The organ distribution data in mice showed that more than 93.0% of the injected dose has accumulated in the lungs with a negligible amount of radioactivity to be detected in the non target organs. The size distribution data showed that 80.0% of the particles occur in the range of 10-80μm. The freeze-dried preparation of Sn-MAA kits (sterile and pyrogen free) were stable for at least 170 day.